2023
DOI: 10.1590/s1984-29612023024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation in vitro of the virulence of two entomopathogenic heterorhabditid nematodes in the control of Stomoxys calcitrans (Diptera: Muscidae) larvae in byproducts of the sugar and alcohol industry

Abstract: Stomoxys calcitrans causes losses to livestock, mainly to cattle. This study aimed to determine the pathogenic potential of Heterorhabditis bacteriophora HP88 and H. baujardi LPP7 against S. calcitrans larvae after being exposed to byproducts of the sugar and alcohol industry. The efficacy of EPNs on stable fly larvae was evaluated in bioassays with vinasse at three temperatures (16, 25 and 35 °C) and concentrations (0, 50 and 100%), as well as in relation to larva age (4, 6 and 8 days) in filter cake and EPNs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Monteiro Sobrinho et al (2023) reported larvae mortality rates of 73.3% in sugarcane bagasse ash. Studies involving H. bacteriophora HP88 and H. baujardi LPP7 to control S. calcitrans larvae in vinasse, filter cake and sugarcane bagasse (Monteiro Sobrinho et al, 2023) also showed higher mortality rates than those found in the present study, even this not using sugarcane substrate that could interfere in the action of H. amazonensis NEPT11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monteiro Sobrinho et al (2023) reported larvae mortality rates of 73.3% in sugarcane bagasse ash. Studies involving H. bacteriophora HP88 and H. baujardi LPP7 to control S. calcitrans larvae in vinasse, filter cake and sugarcane bagasse (Monteiro Sobrinho et al, 2023) also showed higher mortality rates than those found in the present study, even this not using sugarcane substrate that could interfere in the action of H. amazonensis NEPT11.…”
Section: Resultsmentioning
confidence: 99%
“…Entomopathogenic nematodes (EPNs) have emerged as alternatives for use in biological pest control (Kaya & Gaugler, 1993), and these microorganisms have already proved their ability to kill stable fly larvae (Leal et al, 2017;Monteiro Sobrinho et al, 2021), even when the latter are in substrates originating from the sugar and alcohol industry (Monteiro Sobrinho et al, 2016, 2023. Therefore, new species of EPNs must be tested and evaluated in order to increase the alternatives for controlling S. calcitrans.…”
Section: Introductionmentioning
confidence: 99%
“…20-30 °C (Kim and Alston, 2008;Power et al, 2009). In the specific case of HeterorhabditisbaujardiLPP7, an optimal temperature of 28°C for replication and infection had been reported by Sobrinho et al (2023), with emphasis on the origin of this EPN strain, the Amazon rainforest strain; hence, it is probably already adapted to tropical environments (Dolinski et al, 2007). The cold-active EPN species, like S. kraussei, provide an interesting potential for further developments into EPN-based pest control strategies in orchard environments (Willmott et al, 2002).…”
Section: Insect Host Physiologymentioning
confidence: 96%
“…On the other hand, reported the viability of H. baujardi LPP7 at temperatures of 35°C for two hours, with no loss in efficacy against G. mellonella larvae. Whereas, a studyby Sobrinho et al (2023) revealed that H. baujardi LPP7 lost efficacy against larvae of the stable fly Stomoxyscalcitrans (Diptera:Muscidae), after 72 h at 35°C. Moreover, several studies reported the adaptation of different EPN species to temperatures around 35°C (Kusakabe et al, 2019).…”
Section: Insect Host Physiologymentioning
confidence: 99%
“…Evaluation of the effect of Heterorhabditis bacteriophora (HP88) on Stomoxys calcitrans (Linnaeus, 1758) larvae (Diptera: Muscidae) in sugarcane bagasse ash Monteiro Sobrinho et al (2023) reported that EPNs are effective on S. calcitrans larvae in a variety of sugarcane substrates, and sugarcane bagasse ash is a substantial substrate produced by sugar mills, and although it is produced in smaller quantities than vinasse, bagasse and sugarcane straw, it is also used for the fertilization of sugarcane fields, favoring the development of immature stages of the stable fly, which causes significant losses in livestock and in the sugar and alcohol industry (Corrêa at al., 2013).…”
Section: /5mentioning
confidence: 99%